Rorschachova metoda při posuzování dopadů psychologického traumatu - Lečbych, Martin (Československá psychologie, 2014)
The study focuses on possibilities of application of Rorschach method in assessing traumatic experience. Author tries to organize existing knowledge about the image of posttraumatic phenomena in Rorschach method. The author notes that the symptoms of trauma are in Rorschach evidence-based in several basic levels of psychological functioning, i. e. variables associated with lower cognitive performance, variables associated with poor affective control and signs of anxious experience. One of characteristic features is also a long-term projection of topics associated with trauma, the interpretation of ambiguous stimulus with reference to the memories of the traumatic event.
Keywords: Projective Techniques; Stress Disorders, Post-Traumatic; Rorschach Test; lidé; projektivní techniky; Rorschachův test; Humans; posttraumatická stresová porucha